2011
DOI: 10.1093/molbev/msr009
|View full text |Cite
|
Sign up to set email alerts
|

Intragene Higher Order Repeats in Neuroblastoma BreakPoint Family Genes Distinguish Humans from Chimpanzees

Abstract: Much attention has been devoted to identifying genomic patterns underlying the evolution of the human brain and its emergent advanced cognitive capabilities, which lie at the heart of differences distinguishing humans from chimpanzees, our closest living relatives. Here, we identify two particular intragene repeat structures of noncoding human DNA, spanning as much as a hundred kilobases, that are present in human genome but are absent from the chimpanzee genome and other nonhuman primates. Using our novel com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(83 citation statements)
references
References 107 publications
(130 reference statements)
4
78
1
Order By: Relevance
“…The stop-TAA CLT has a significant extension, but is of very low frequency. On the other hand, the extension of stop-TAG CLT is sizably larger in some non-alpha satellite HORs, which have primary repeat units of 1.6, 2.4, and 0.55 kb 32,33 sizably larger than alpha satellites (~0.171 kb).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The stop-TAA CLT has a significant extension, but is of very low frequency. On the other hand, the extension of stop-TAG CLT is sizably larger in some non-alpha satellite HORs, which have primary repeat units of 1.6, 2.4, and 0.55 kb 32,33 sizably larger than alpha satellites (~0.171 kb).…”
Section: Resultsmentioning
confidence: 97%
“…As a case study, this new method is applied to the following DNA sequences: to human and chim-panzee alpha satellite consensus HORs, to monomeric alpha satellite regions and to no-repeat DNA regions (Table 1 and Supplementary table S1). In these studies the consensus sequences are determined by GRM analysis [25][26][27][28][29][30][31][32][33] of the recent Build 37.2 assembly (Figure 1). First the dinucleotide frequencies in consensus alpha satellites are analyzed (Supplementary table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This HOR pattern is not found in chimpanzee and shows some peculiarities, namely that the repeat unit is much longer than most primary repeat units identified so far and that the HOR is fully embedded within a gene. Additionally, the total absence of tandem repeats of NBPF HOR copies in chimpanzees while 47 tandem repeat HOR copies are present in human genomes reflects a human accelerated HOR pattern that distinguishes humans from nonhuman primates ( Figure 4B) (Paar et al, 2011). It has been shown that genes with an important contribution to human evolution, like the NBPF gene family, are located in human segmental duplications, which are frequently organised around core duplicons (Jiang et al, 2007).…”
Section: The Nbpf Gene Family and Human Evolutionmentioning
confidence: 97%
“…Figure not drawn to scale. B/ The total number of NBPF monomers and the number of NBPF HOR copies (both tandemly organised and dispersed) gradually increases with evolutionary development, but the tandem repetition of the NBPF HOR copies is exclusive to humans (Modified after Paar et al, 2011, Oxford Journals (2011, reproduced by permission).…”
Section: The Nbpf Gene Family and Human Evolutionmentioning
confidence: 99%